RNA Sequencing Analysis of Metopolophium dirhodum (Walker) (Hemiptera: Aphididae) Reveals the Mechanism Underlying Insecticide Resistance - Gao, Haifeng; Zhu, Xun; Li, Guangkuo; Liu, Enliang; Shen, Yuyang; Zhao, Sifeng; Ge, Feng (Frontiers in Sustainable Food Systems, 2021)
Xinjiang (XJ) and Ningxia (NX) provinces are important agricultural regions in western China. Aphids are one kind of the most devastating pests in both the provinces. Aphids are typical phloem-feeding insects distributed worldwide and can severely damage crops. In this study, two representative Metopolophium dirhodum (Walker) (Hemiptera: Aphididae) populations were collected from the typical agricultural regions of XJ and NX, respectively for a high-throughput transcriptome sequencing analysis. A total of 5,265 differentially expressed genes (DEGs) were identified. The functional annotation of DEGs and the identification of enriched pathways indicated many of the DEGs are involved in processes related to energy metabolism, development, and insecticide resistance. Furthermore, an investigation of insecticide toxicity revealed the NX population is more resistant to insecticide treatments than the XJ population. Thus, the transcriptome data generated in present study can be used for functional gene characterization relevant to aphid development, metabolism, environmental adaptation, and insecticide resistance.